Migration dynamics and the devolution agenda in Matabeleland South Province of Zimbabwe - N. Mtombeni; V.M. Matiza (African Journals on line (AJOL), 2022)
Economic challenges in Zimbabwe have seen most people relocating to different countries in a bid to earn a decent living. These movements are done at all levels, whether learned or general/ domestic workers. In doing so, a lot of brain drain is witnessed where many technical and expert personal are no longer offering their services to their home countries but elsewhere. The government of Zimbabwe has come up with a statutory instrument to grow the Zimbabwean economy at Provincial level so as to become an upper middle economy by 2030. With this challenge at hand, migration of these people has a lot of implication on the government’s devolution agenda as the local people are moving away from developing their area. Against this backdrop, the paper seeks to bring out migration dynamics in Matabeleland South Province which may hinder government efforts in achieving the agenda in the Province. Most of the people in the province are a source of cheap labour in the neighbouring South Africa and possibly Botswana. Using qualitative research methods, the researchers purposively sampled some families in Gwanda and conveniently selected some government departments to establish the purpose and impact of the devolution program. Through some interviews carried out, the research established that many people especially youths in the Province migrate to South Africa as cheap labour and that impacts negatively on the devolution agenda and the vision 2030 in the Province. As a result the researchers therefore recommend that the government of Zimbabwe should put in place stringent measures at the boarder places so that the easy flow of human traffic as boarder jumpers is curbed.